2019
DOI: 10.1073/pnas.1821970116
|View full text |Cite
|
Sign up to set email alerts
|

Directional soliton and breather beams

Abstract: Solitons and breathers are nonlinear modes that exist in a wide range of physical systems. They are fundamental solutions of a number of nonlinear wave evolution equations, including the unidirectional nonlinear Schrödinger equation (NLSE). We report the observation of slanted solitons and breathers propagating at an angle with respect to the direction of propagation of the wave field. As the coherence is diagonal, the scale in the crest direction becomes finite; consequently, beam dynamics form. Spatiotempora… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 35 publications
0
12
1
Order By: Relevance
“…The estimated wave period roughly corresponds to the dominant wave in the observed spectrum (Figure 1). Unlike the directional soliton studied in Chabchoub et al [8], the observed wave group is confined in the propagation direction as well. Longcrested envelope solitons are known to be unstable to transverse perturbation (e.g., [28]).…”
Section: Reconstructed Directional Wave Groupcontrasting
confidence: 60%
See 3 more Smart Citations
“…The estimated wave period roughly corresponds to the dominant wave in the observed spectrum (Figure 1). Unlike the directional soliton studied in Chabchoub et al [8], the observed wave group is confined in the propagation direction as well. Longcrested envelope solitons are known to be unstable to transverse perturbation (e.g., [28]).…”
Section: Reconstructed Directional Wave Groupcontrasting
confidence: 60%
“…The theoretical framework of the directional wave group follows Chabchoub et al [8]. By applying a coordinate transformation, T = t cos θ − y c g sin θ , the 2D+T NLSE reduces to a 1D+T NLSE in which stable planar wave solutions exist.…”
Section: Directional Coherent Wave Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…Preprocessing was done with a bandpass filter with a bandwidth from 20 min to 2.5 h. Visual analysis of the filtered time series of observations in the area of Cape Castricum revealed wave packets covering waves with a period of about 1.6 h. The wave packets occurred in groups of approximately 6 waves and appear to be synchronized with the beginning of the K1 (diurnal) tide. It is conjectured that the detected waves can be attributed to soliton-like oscillations or breathers [1][2][3][4][5][6], in which the oscillations are modulated within a soliton-like envelope. In work [6, p. 9759], the definition of soliton-like waves and breathers is given: "… these are nonlinear modes existing in a wide range of physical systems.…”
mentioning
confidence: 99%